Restoration - Ólafur Jóhann Ólafsson (Ecco, 2012)
Returning home to La Foce, a crumbling villa in Tuscany, to make amends with her husband, Iris is caught between loyalists and resistors, cruel German forces and Allied troops, and, while struggling to survive, hopes that the life and love she lost can one day be restored.